THIRD PARTY OBJECTION AND ACTION AGAINST ENFORCEMENT (REQUEST FOR EXCLUSION) - Salma, Marija (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
This paper deals with a right of a third party to prevent enforcement on the basis of a claim and evidence that rights or assets seized in enforcement proceeding belong to him (third party) and not to the enforcement debtor. In most of jurisdictions that were subject of analysis of this paper, this right of a third party is exercised by filing an objection to the court conducting enforcement proceedings. The claim of the third party is directed towards the enforcement creditor as well as against the enforcement debtor. In the event the claim of the third party is being contested, the court instructs the third party to initiate litigation proceedings for determining whether the third party is entitled to exclusion of such rights or assets from enforcement, especially if such third party holds property rights or some other rights over the assets that are being subject to enforcement proceedings. In majority of analyzed jurisdictions, enforcement proceedings are being suspended provided the third party, in the objection being filed makes prima facie likely, on the basis of credible evidence, that his assets were seized in the enforcement proceedings. However, according to the law of the Republic of Serbia, a credible objection of a third party does not result in suspension of enforcement proceedings, something that is being criticized in this paper. As a result of this provision of the law, a bona fide third party is forced to endure the enforcement although his claim has been made likely and subsequently confirmed in the litigation proceedings. The author, in particular, points to the legal consequences of mala fide enforcement creditor that knew that the assets that are being subject of the enforcement proceedings do not belong to the enforcement debtor. The author is of the opinion that, in such cases, the enforcement creditor should be obliged to pay to the third party damages that such party suffered as a result of enforcement proceedings being instigated against his assets.